ANALISIS PAJAK PER TAMBAHAN NILAI (PPN) TERHADAP STABILITAS EKONOMI MAKRO - Dini Vientiany; Nabilah Irwani; Nesya Aulia; Saibarani Nabila (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The aim of this research is to analyze the impact of Value Added Tax (VAT) on macroeconomic stability in Indonesia. This research aims to understand how VAT affects macroeconomic variables such as Gross Domestic Product (GDP) growth, inflation, interest rates and exchange rates. Thus, it is hoped that this research can provide a better understanding of the relationship between VAT and macroeconomic stability in Indonesia. This research uses a qualitative approach with document analysis methods. The qualitative method was chosen because it allows researchers to understand in depth the relationship between VAT and macroeconomic stability in Indonesia. Document analysis was chosen as a data collection technique because it allows researchers to collect and analyze various sources of information relevant to this research. Based on the results of the research and data analysis that has been carried out, it can be concluded that Value Added Tax (VAT) has a positive relationship with macroeconomic stability in Indonesia. This is shown through several main indicators. First, VAT revenue and growth in Gross Domestic Product (GDP).